Activation of KATP channels in pain modulation: a systematic review of preclinical studies - Signe Schønning Beich; Lili Kokoti; Mohammad Al-Mahdi Al-Karagholi; Mohammad Al-Mahdi Al-Karagholi (Frontiers in Physiology)
ObjectiveTo systematically review the involvement of KATP channel activation in pain modulation in preclinical studies.BackgroundKATP channels are expressed at several levels in the spinal and trigeminal pain pathways, where they seem to modulate nociceptive transmission.MethodsPubMed and Embase databases were searched until 29 January 2024, using the following search string: [(pain) OR (nociception) OR (antinociception) AND (KATP channel) OR (ATP sensitive potassium channel)]. Non-English and unavailable records, as well as records with non-experimental methodology, were excluded. Inclusion criteria were preclinical studies measuring pain in vivo upon activation of the KATP channel by administering a stimulator or positive modulator. Records were screened based on title and abstract, and those that met the study inclusion criteria were reviewed based on study design, measurements, intervention, and outcomes.ResultsThe search resulted in 569 records. In total, 126 duplicates were detected. Subsequently, 438 records were screened by title and abstract, resulting in the exclusion of 396. Based on inclusion criteria, 42 studies were included. The main findings of the present systematic review were that KATP channel openers can attenuate induced pain in various animal models and potentiate the effects of analgesics.ConclusionLocal, systemic, spinal, and supraspinal activation of KATP channels can attenuate pain and potentiate the efficacy of analgesic drugs. One exception was levcromakalim, as the systemic levcromakalim administration, but not a local application, induced pain. This finding is consistent with those of recent human trials. Future studies should investigate the differences in KATP channel activation between rodents and humans, as well as the differences in activation sites between levcromakalim and other KATP channel openers.